Voltage regulation-based sensorless position observer with high-frequency signal injection topology for BDFIGs in ship power microgrid systems. (September 2022) - Hussien, Mohamed G.; Liu, Yi; Xu, Wei; Ismail, Moustafa Magdi
Highlights: The aim of this paper is to propose a new rotor position observer based on the approach of high-frequency signal (HFS) injection for sensorless direct voltage control (DVC) strategy of the stand-alone brushless doubly-fed induction generators (BDFIGs). The proposed new observer is relied on the injection of HFS into the control winding (CW) side, (CW-HFS), while the resulted induced signal detected from the power winding (PW) side will observe the information of rotor position. The suggested new sensorless control method neither need any saliencies in the rotor side nor require any flux computation process, which can ensure the simplicity and efficacy of the proposed method. Comprehensive experimental results are obtained with a prototype wound-rotor BDFIG. The corresponding results ensure the capability and efficacy of the suggested sensorless DVC strategy based on the proposed rotor position observer using the CW-HFS injection approach with a good transient behavior under different operating conditions for the stand-alone BDFIG systems. Abstract: The aim of this paper is to propose a new rotor position observer based on the approach of high-frequency signal (HFS) injection for sensorless direct voltage control (DVC) strategy of the stand-alone brushless doubly-fed induction generators (BDFIGs). The proposed new observer is relied on the injection of HFS into the control winding (CW) side, (CW-HFS), while the resulted induced signal detected from the power winding (PW) side will observe the information of rotor position. The suggested new sensorless control method neither need any saliencies in the rotor side nor require any flux computation process, which can ensure the simplicity and efficacy of the proposed method. Comprehensive experimental results are obtained with a prototype wound-rotor BDFIG. The corresponding results ensure the capability and efficacy of the suggested sensorless DVC strategy based on the proposed rotor position observer using the CW-HFS injection approach with a good transient behavior under different operating conditions for the stand-alone BDFIG systems.